PENGARUH TENAGA KERJA DAN INDEKS PEMBANGUNAN MANUSIA (IPM) TERHADAP PRODUK DOMESTIKREGIONAL BRUTO (PDRB) DI KABUPATEN SIDENRENG RAPPANG - Hatta, Muhammad; Nur, Muhammad; Salvianti, Evi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2021)
Economic development is inseparable from economic growth. Economic growth is one of the measuring tools to measure regional economic conditions. Regional economic growth is an indicator of the success of regional economic development. This study aims to determine the effect of labor and Human Development Index on Gross Regional Domestic Product in Sidenreng Rappang district and to determine which variables are more dominant in influencing Gross Regional Domestic Product income in Sidenreng Rappang district. This study uses a type of quantitative research. The data source comes from the documentation. The population in this study is the workforce and the human development index and Gross Regional Domestic Product, using a 10 year sample. The data analysis technique in this study used multiple linear regression analysis with the help of SPSS 25 software. The results showed that simultaneously the independent variables had a significant and positive relationship with the dependent variable. Partially, the labor variable has no effect and is not significant, while the human development index variable has a positive and significant effect on Gross Regional Domestic Product. The results of the regression value of R square (R2) of 0.982 means that the independent variable explains that labor and the human development index have an effect of 98.2% while the remaining 1.8% is influenced by other variables outside the study.